Natural Products Isolated from Oriental Medicinal Herbs Inactivate Zika Virus - Mariana N. Batista; Ana Cláudia S. Braga; Guilherme Rodrigues Fernandes Campos; Marcos Michel Souza; Renata Prandini Adum de Matos; Tairine Zara Lopes; Natalia Maria Candido; Maria Leticia Duarte Lima; Francielly Cristina Machado; Stephane Tereza Queiroz de Andrade; Cíntia Bittar; Maurício L. Nogueira; et al. (Viruses, 2019)
Zika virus (ZIKV) has been associated with serious health conditions, and an intense search to discover different ways to prevent and treat ZIKV infection is underway. Berberine and emodin possess several pharmacological properties and have been shown to be particularly effective against the entry and replication of several viruses. We show that emodin and berberine trigger a virucidal effect on ZIKV. When the virus was exposed to 160 µM of berberine, a reduction of 77.6% in the infectivity was observed; when emodin was used (40 µM), this reduction was approximately 83.3%. Dynamic light scattering data showed that both compounds significantly reduce the hydrodynamic radius of virus particle in solution. We report here that berberine and emodin, two natural compounds, have strong virucidal effect in Zika virus.